Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/app10031170
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Acoustical Environment in A Shopping Mall and Its Correlation to the Acoustic Comfort of the Workers

Abstract: Noise in shopping centers and restaurants can reduce intelligibility and affect the comfort of the employees working for long periods in such environments. In this study, the interior acoustics of a shopping mall are studied by measuring the reverberation time (RT), with no occupation, and the equivalent sound pressure levels (L Aeq ), with occupations at different times of the day, over a period of one week. The measurements were done at different locations, chosen based on their usage (shopping areas, entran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…However, analyzing the relationship between L A,eq and listening conditions, no correlation was found. In a study conducted on a shopping mall [65], the employees' responses showed a correlation between the loudness in the mall and the reverberation time, as in this study, without any relationship with noise levels.…”
Section: Subjective Evaluation Of Is and G Hall Acoustics And Its Rel...supporting
confidence: 68%
“…However, analyzing the relationship between L A,eq and listening conditions, no correlation was found. In a study conducted on a shopping mall [65], the employees' responses showed a correlation between the loudness in the mall and the reverberation time, as in this study, without any relationship with noise levels.…”
Section: Subjective Evaluation Of Is and G Hall Acoustics And Its Rel...supporting
confidence: 68%
“…The visitors were not aware of the impact of the malls' high sound level on their hearing health. However, the workers might experience otherwise, as a study in shopping malls in Jordan found malls' workers experienced headaches because of the recurring high noise level (Alnuman and Altaweel 2020). It is vital to integrate safe acoustic levels into shopping malls for the health of both the workers and the visitors.…”
Section: Test Of Independencementioning
confidence: 99%
“…A study in the UK analyzed the acoustic comfort where shopping malls have been in the country for a long time (Chen and Kang 2004). A study showed acoustic comfort in shopping malls in Jordan, but there were no mentions of the cultural background (Alnuman and Altaweel 2020). A study in Russia investigated acoustic treatment significantly improved the soundscape in shopping malls (Kanev 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Alnuman and Altaweel [39] studied a large shopping mall in the very centre of Amman, Jordan, and chose shopping areas, entrances, food courts, and playing areas to explore the sound environment and its correlation to the acoustic comfort of the workers. L Aeq-3min were collected between 10:30 and 12:30, between 13:30 and 15:30, between 16:30 and 18:30, between 19:30 and 21:30 during the entire seven-day period.…”
Section: Shopping Mallsmentioning
confidence: 99%